Smartphone usage and preferences among postpartum HIV-positive women in South Africa - Mogoba, Pheposadi L (Department of Public Health and Family Medicine, 2019)
Introduction. In South Africa, HIV-positive women receiving antiretroviral therapy (ART) often are lost to care postpartum and strategies to support long-term engagement in care are needed. Mobile health (mHealth) interventions are emerging as potential strategies for supporting long-term engagement in the prevention of mother-to-child transmission (PMTCT) of HIV care continuum. Smartphone technology and mobile data are getting cheaper and more accessible, however little research has been done to explore the potential for smartphone-based interventions in the PMTCT cascade in low-resource settings. This study explored smartphone use and the acceptability and feasibility of mHealth interventions among postpartum women who were attending the Gugulethu Community Health Centre in Cape Town, South Africa.